The Role of Clinical Pharmacists in the Management of Atopic Dermatitis - Putri Diana Nurul Adha (Publikasi Indonesia, 2024)
Atopic dermatitis (AD) is a chronic inflammatory skin condition characterized by itchy, inflamed skin that affects a significant portion of the population, particularly children, and can significantly impact quality of life. The role of clinical pharmacists in managing AD has gained prominence due to their expertise in medications, patient education, and collaborative care. This article explores the various ways clinical pharmacists contribute to the comprehensive management of AD, emphasizing patient education, medication management, and interprofessional collaboration.